A theoretical framework on factors causing delay of construction industries projects - Ahmed Al-Fadhali, Najib Mohammed; Zainal, Rozlin (Medwell Jommls, 2017)
Time is one of the main important elements which should be taken into consideration during implementation of construction industry projects and project management life cycle as a whole and can be considered as one of the most significant parameters of a project and the main critical factor that determines the success of the project. The objective of this study is to propose the theoretical framework that causes construction projects delay in Yemen. The causes of delay were collected from the prior intemational jownal papers. Time delay is a very recurrent phenomenon and is nearly associated with almost all constructing projects. However, little effort has been made to amputate the phenomenon. Delay can be defined as time overnm or expansion of time to accomplish the project. Construction delay cannot be avoided especially in government facilities in Yemen. Therefore, delay is a case when the actual work of a construction project is slower than the planned schedule or late accomplishment of the projects. The review of literature in relation to causes of delay in construction projects can be summarized llllder 3 main headings namely: delay caused by contractor, delay caused by acts of God and delay caused by consultant. These 3 variables form the framework upon which this review is based.